Welfare Evaluation of Pet Dogs Through Feeding Protocols Followed, Nutritional Composition of Available Feeds and Blood Metabolic Profile - Beigh, Yasir Afzal; Sayima Akhter; Ganai, Abdul Majeed; Ahmad, Haidar Ali; Javid Farooq (Indian Journal of Animal Nutrition, 2026)
A survey was conducted in Central Kashmir covering 91 adult pet dogs with collection of 26 feed and 73 blood samples. Feeding practices followed by the dog owners were recorded and samples of commercial dry adult dog feed brands collected during survey were subjected to nutritional analysis to assess their effects on blood metabolic profile. Mostly ( 63%) the pet dogs were reared on homemade diets with about 90% receiving non-vegetarian type, and only 5% were exclusively fed commercial dog feeds of different brands. Majority (63%) of the pet dogs were fed thrice a day. Percentage of available commercial dog feed samples having nutrient composition below than the recommended standards were 19%, 15%, 31%, 12% and 15% for protein, fat, fibre and calcium, total ash, and phosphorus, respectively. The homemade diets had wide variation in composition and were generally imbalanced. In blood metabolic profile, there was wider prevalence of calcium deficiency especially in pet dogs fed homemade diets with 51%, 44% and 30% of the plasma samples exhibited higher cholesterol, triglycerides and plasma urea-nitrogen values, respectively than normal physiological ranges. The study concludes that homemade diets constitute the mainstay of feeding with little or no provision of supplements to pet dogs, but these diets are nutritionally imbalanced. It is recommended that dog owner need to consult the animal nutritionist /veterinarian to make proper diet charts for meeting the nutritional requirements of their pets.